Community Development to Feed the Family in Northern Manitoba Communities: Evaluating Food Activities based on Their Food Sovereignty, Food Security, and Sustainable Livelihood Outcomes - Thompson, Shirley; Kamal, Asfia Gulrukh; Alam, Mohammad Ashraful; Wiebe, Jacinta (Canadian journal of nonprofit and social economy research, 2012)
ABSTRACT This article explores food-related activities and their impacts on sustainable livelihood assets, food sovereignty, and food security, and provides insight for future food-related community development. Analysis is based on community food assessments conducted in 14 Northern Manitoba communities and included a food security survey, price survey, and interviews. The lack of community control over development in First Nation and other Northern remote and rural communities in Northern Manitoba is found to undermine both food sovereignty and sustainable livelihoods, while creating high levels of food insecurity. According to logit models, sharing country foods increases food sovereignty and sustainable livelihoods, and has a stronger relationship to food security than either road access to retail stores in urban centres or increased competition between stores. The model predicts that rates of food insecurity for a community with a country foods program and with access to public transit and roads at 95% would be lower than the Canadian average of 92%. RÉSUMÉ Cet article explore les activités relatives à l’alimentation et leur impact sur les biens durables ainsi que sur la souveraineté et la sécurité alimentaires tout en ouvrant des perspectives sur le développement communautaire futur relatif à l’alimentation. L’analyse se fonde sur une recherche menée dans quatorze communautés du nord du Manitoba et comprend un premier sondage sur la sécurité alimentaire, un second sondage sur les prix, et des entrevues. Le manque de contrôle du développement dans les communautés reculées du nord du Manitoba, tant autochtones que non-autochtones, mine à la fois la souveraineté alimentaire et les moyens d’existence durables tout en provoquant de hauts niveaux d’insécurité alimentaire. Selon un modèle Logit, le partage d’aliments locaux permet une souveraineté alimentaire et une autonomie durable tout en ayant un meilleur impact sur la sécurité alimentaire que celui obtenu par l’accès routier aux supermarchés des centres ...